Monotropein Attenuates Nuclear Factor Kappa B Activity there by Ameliorates Mycoplasma pneumoniae Triggered Pneumonia in Rodent Model - Fan, Jiaying; Zhao, Lin (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Pneumonia is a prevalent acute respiratory illness that impacts the alveoli and the distal airways and if left untreated, it presents a significant health challenge. It is linked to elevated rates of illness and death across all age groups worldwide. The treatment of pneumonia has become increasingly difficult due to antibiotic resistance, which complicates management strategies and leads to poorer patient outcomes. The rise of multi-drug resistant pathogens requires the use of stronger and often more toxic antibiotics, heightening the risk of adverse effects and further health complications. Materials and Methods: In this research, our objective was to investigate the efficacy of the phytochemical monotropein in mitigating bacterial pneumonia triggered by Mycoplasma pneumoniae in a rodent model. Swiss albino mice with pneumonia were administered monotropein and their antimicrobial and anti-inflammatory responses were assessed. The pathogen clearance capability of monotropein was evaluated by measuring lung weight index, nitric oxide and myeloperoxidase levels. Moreover, we quantified antioxidant levels to determine monotropein's ability to scavenge oxidative stress in the context of pneumonia infection. To assess the anti-inflammatory effects of monotropein, we examined the levels of inflammatory cytokines, corroborated by total cell counts in Bronchoalveolar Lavage Fluid (BALF) and lung tissue DNA content. Additionally, NF-kB levels were quantified to assess monotropein's capacity to enhance the host defense mechanisms against pneumonia. Histopathological analyses of the lung tissue were performed to validate the beneficial effects of monotropein on Mycoplasma pneumoniae-induced pneumonia. Results: The findings of our study demonstrate that monotropein treatment markedly decreased levels of nitric oxide and myeloperoxidase, effectively preventing pulmonary edema in mice exposed to Mycoplasma pneumoniae. Furthermore, it inhibited oxidative damage and DNA harm in the pneumonic mice. The treatment also led to a considerable reduction in inflammatory cytokines and NF-kB levels, supporting the anti-inflammatory properties of monotropein against pneumonia. Histopathological evaluations confirmed the beneficial effects of monotropein in the pneumonia-induced rodent model. Conclusion: Overall, our findings indicate that monotropein is a powerful antioxidant and anti-inflammatory substance that effectively mitigates pneumonia infection. These promising results suggest that monotropein warrants further investigation for potential development as a compound for the management of pneumonia.
Keywords: Bacterial Pneumonia; Inflammation; Monotropein; Mycoplasma pneumoniae; NFkB; Phytochemical Drug